Rethinking Density. Art, Culture, and Urban Practices - Batista, Anamarija; Kovács, Szilvia; Lesky, Carina (Publication Series of the Academy of Fine Arts Vienna, 2017)
Rethinking Density: Art, Culture, and Urban Practices considers new perspectives and discussions related to the category of density, which for a long time has been part of urban-planning discourses and is now regaining the attention of artists and practitioners from a number of different disciplines. In an interplay of models, coping strategies, and experimental approaches, this publication combines research from cultural studies, artistic research, sound studies as well as architectural and urban theory. The issues discussed include the consideration of retroactive architectural design as a means to retrace the historical layers of a city, a proposal for spacesharing concepts as instruments for urban revitalization processes, and a case study on the potential for new sonic social spaces as subversive modes to undermine prevailing power structures.